40th International Conference on Environmental Systems 2010
DOI: 10.2514/6.2010-6135
|View full text |Cite
|
Sign up to set email alerts
|

Overview of NASA's Thermal Control System Development for Exploration Project

Abstract: NASA's Constellation Program includes the Orion, Altair, and Lunar Surface Systems project offices. The first two elements, Orion and Altair, are manned space vehicles while the third element is broader and includes several subelements including Rovers and a Lunar Habitat. The upcoming planned missions involving these systems and vehicles include several risks and design challenges. Due to the unique thermal environment, many of these risks and challenges are associated with the vehicles' thermal control syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…3 Future Lunar and Mars missions will require turndown ratios as high as 12:1, which has spurred investigation of variable heat rejection radiators. 7 Deployable radiators, which use a shape memory alloy (SMA) actuator to open and close louvered panels comprised of high-conductivity graphite composite tape, have been thermal vacuum chamber tested and displayed encouraging thermallyactivated actuation for passive heat control. [8][9][10] Most recently, this concept has achieved a turndown ratio of 16:1 and been selected for integration on the DESTINY + in-space technology demonstrator for operational environment validation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Future Lunar and Mars missions will require turndown ratios as high as 12:1, which has spurred investigation of variable heat rejection radiators. 7 Deployable radiators, which use a shape memory alloy (SMA) actuator to open and close louvered panels comprised of high-conductivity graphite composite tape, have been thermal vacuum chamber tested and displayed encouraging thermallyactivated actuation for passive heat control. [8][9][10] Most recently, this concept has achieved a turndown ratio of 16:1 and been selected for integration on the DESTINY + in-space technology demonstrator for operational environment validation.…”
Section: Introductionmentioning
confidence: 99%
“…A novel hardware component called the Sublimator Driven Coldplate (SDC) has been developed under NASA’s Constellation Program. It targets equipment which has a low heat load, short transport distance, and short mission duration requirements, and which has the potential to replace an entire thermal control system with one hardware component [ 20 ]. Kim et al have suggested a new spacecraft thermal control hardware system composed of two parallel channels working for a heat pipe (HP) and a solid–liquid phase change material (PCM) for a high heat dissipating component which works intermittently with short duty [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The turndown ratio, defined as the ratio between the maximum and minimum heat rejection capabilities of the TCS, is a primary measurement of TCS performance . 2 More precisely, this ratio involves the maximum heat rejection rate in the hottest environment and the miminimum heat rejection rate in the coldest environment. The turndown ratio of a TCS is therefore measured relative to the particular thermal environments in which it is designed to operate.…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have been undertaken to improve TCS performance through the development of variable heat rejection radiators. 5 Examples include roll-out fin radiators , 6 freezable radiators , 2 digital radiators , 7 and variableemissivity radiators . [8][9][10][11] This work supports the development of a novel type of radiator, known as a variable-geometry or morphing radiator , 12 and provides details regarding the thermal characterization of various prototypes that were built.…”
Section: Introductionmentioning
confidence: 99%